2023
DOI: 10.1002/vnl.21980
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and rheology of titanium dioxide nanoparticles loaded κ‐carrageenan hydrogel beads strengthened by mixed salts for multipollutant water remediation

Abstract: Hydrogel beads are emerging as alternate adsorbent material for the batch or continuous column treatment of dye wastewater. Polysaccharide-based gel beads are preferred for their uniform shape and size, large specific surface area, and easy separation by filtration and subsequent reuse. In this work, we prepare and rheologically characterize UV-active κ-carrageenan/TiO 2 beads for the adsorption and degradation of dyes. The 3-4 mm sized nanocomposite beads are formed by the extrusion of κ-carrageenan/TiO 2 gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The FTIR spectra of the unloaded and drug-loaded κ-carrageenan/olive oil emulsion gels are shown in Figure S7. Table S1 describes the functional groups present in κ-carrageenan, olive oil, vitamin C, and curcumin. ,, On formation of the κ-carrageenan/olive oil emulsion gel (OCR = 3:7), we observe additional peaks at 2923, 2853, 1743, 1462, and 721 cm –1 as compared to the κ-carrageenan powder. With the addition of vitamin C to the κ-carrageenan/olive oil (3:7) emulsion gel, new peaks at 1681, 1190, and 1111 cm –1 are detected.…”
Section: Resultsmentioning
confidence: 98%
“…The FTIR spectra of the unloaded and drug-loaded κ-carrageenan/olive oil emulsion gels are shown in Figure S7. Table S1 describes the functional groups present in κ-carrageenan, olive oil, vitamin C, and curcumin. ,, On formation of the κ-carrageenan/olive oil emulsion gel (OCR = 3:7), we observe additional peaks at 2923, 2853, 1743, 1462, and 721 cm –1 as compared to the κ-carrageenan powder. With the addition of vitamin C to the κ-carrageenan/olive oil (3:7) emulsion gel, new peaks at 1681, 1190, and 1111 cm –1 are detected.…”
Section: Resultsmentioning
confidence: 98%
“…This indicates that there was no persistent deformation of the material after the tension or strain was removed. Time-dependent behavior emerges as stress or strain is increased within the linear viscoelastic zone . The pace of stress or strain application affects its response, which is a mix of viscous flow and elastic deformation.…”
Section: Resultsmentioning
confidence: 99%
“…Timedependent behavior emerges as stress or strain is increased within the linear viscoelastic zone. 52 The pace of stress or strain application affects its response, which is a mix of viscous flow and elastic deformation. It can be clearly observed that the onset of slope change is diagonally shifted toward the right or higher shear rate region.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thareja et al characterize the rheology of such systems made with titanium dioxide (TiO 2 ) nanoparticles in an adsorbent polysaccharide (κ‐carrageenan) gel cross‐linked with mixed salts. [ 14 ] Neal, Calabrese, et al studied magnetically and thermo‐responsive materials. [ 15 ] They describe the influences of application of magnetic field and/or incorporation of nanosilica on phase change behavior in the material systems.…”
Section: Descriptions Of Articles In the Special Issuementioning
confidence: 99%